The macroeconomic impact of structural policies on labour market outcomes in OECD countries: a reassessment - Gal, Peter N.; Theising, Adam (Paris, 2015)
"This paper presents a first set of updates and extensions of the large body of existing evidence about the aggregate labour market impact of structural policies, in the context of enhancing the OECD’s supply-side framework for the quantification of reform packages. In line with previous findings, elements of the tax benefit system, activation policies and wage setting institutions are found to be robust policy determinants of the aggregate employment and unemployment rates. Looking beyond the overall employment impact, outcomes for vulnerable groups such as the low educated, the youth and the elderly tend to be more affected by certain structural policies, including specific measures targeted at them. Finally, more competition-friendly product market regulations are also found to impact aggregate employment rates positively and significantly, although less robustly."